Research of the Meshing Characteristic of Bi-directional Arc Cylindrical Gear - Tian Deyun; Song Aiping; Zhang Yihan; Shen Yuhan (Jixie chuandong)
A new type of gear bi- directional arc cylindrical gear is proposed,the tooth trace of the gear is arc,the bending resistance strength of the gear can be increased and the axial force of the gear transmission can be eliminated. In the processes of gear transmission meshing,it is convex surface and concave surface contact transmission,the carrying capacity of the gear is increased,the wear of the tooth surface is decreased,the service life of the gear is improved. The gear pair meshing character is researched and its contour curve equation,meshing line equation and transmission ratio are derived. reach A conclusion that the gear pair possess the advantages of constant transmission ratio and stable transmission is obtained.